Walkability Concept Toward Sustainable City: Comparative Insights of Brisbane and Bogor Urban Areas - Yazid, Hana; Hasibuan, Hayati Sari; Koestoer, Raldi Hendro (Indonesian Journal of Environmental Management and Sustainability, 2023)
A successful sustainable city prioritizes humans by integrating the transportation system with urban development. One of which is considering walkability. The walkability concept is important since walking reduces congestion, promotes low environmental impacts, and possesses social and economic values. Land use integration with walkable pedestrian facilities is a challenge for stakeholders in creating policies to actualize a sustainable city. This paper reviews the walkability condition and policies concerning pedestrian facilities in Brisbane, Australia and Bogor, Indonesia. Bogor was selected due to its strategic location as Jakarta’s satellite city. Method used was literature review with comparative analysis, analyzing similarities, differences, advantages, and disadvantages of urban policies in prioritizing humans to achieve walkable and sustainable city in Australia and Indonesia. The indicators determining Brisbane community’s behavior to walk are distance to destination (59%), travel time (14%), hot weather (19%), roads with various altitudes (4%), lack of paths (3%), and lack of green areas (1%). In Bogor, Indonesia, pedestrian facilities are lacked for people with special needs, elderlies, children, and pregnant women (16.5%), unsafe crossing facilities (19.8%), and unsafe rider behaviors (15.8%). Policies related to walkability can be used as a basis to influence the behavior of urban communities in walking, to achieve the shared goal: a sustainable city.